Evaluation of sustainability of university campuses: The evaluation of Bursa Uludag University Görükle Campus according to UI Green Metric Word University Ranking - Altun, Gamze; Zencirkıran, Murat (TeMA - Journal of Land Use, Mobility and Environment, 2023)
In this study, a total of six categories belonging to the International Green Metric (UI Green Metric) index by applying observational and physical analyzes to Bursa Uludağ University (BUU) Görükle Campus; structure and infrastructure (15%), energy and climate change (21%), waste (18%), water (10%), transportation (18%) and education (18%) and 51 evaluation criteria that define these categories. As a result of the evaluation, the university’s estimated UI Green Metric score for 2021 was calculated. As a result of the calculations, the estimated total success of BUU Görükle Campus was determined as 5775. The highest success rate was obtained from the Education and Research (ED) (97.22%) category, while the lowest success rate was obtained from the Energy and Climate Change (EC) (39.29%) category.